2006
DOI: 10.1021/ja065754d
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic, Enantioselective Bifunctional Inverse Electron Demand Hetero-Diels−Alder Reactions of Ketene Enolates and o-Benzoquinone Diimides

Abstract: In this Communication, we report a system in which an achiral Lewis acid (activating the diene) works in concert with a chiral nucleophile (dienophile) to effect the first highly enantio- and regioselective catalytic inverse electron demand Diels-Alder [4 + 2] cycloaddition reaction to form biologically active quinoxalinones from ketene enolates and o-benzoquinone diimides in good to excellent yields with >99% ee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(44 citation statements)
references
References 19 publications
1
43
0
Order By: Relevance
“…Lower enantioselectivities were achieved with other quinines. The same catalytic system has been applied to the cycloaddition of ketene enolates with o-benzoquinone imides 112 and o-benzoquinone diimides, 113 affording the corresponding 1,4-benzoxazinones and quinoxalinones, respectively, in excellent enantioselectivities.…”
Section: Dielsealder Reactionsmentioning
confidence: 99%
“…Lower enantioselectivities were achieved with other quinines. The same catalytic system has been applied to the cycloaddition of ketene enolates with o-benzoquinone imides 112 and o-benzoquinone diimides, 113 affording the corresponding 1,4-benzoxazinones and quinoxalinones, respectively, in excellent enantioselectivities.…”
Section: Dielsealder Reactionsmentioning
confidence: 99%
“…2b). 29 Another more recent member in this family of chiral intermediates is the ammonium dienolate 6 derived from γ-deprotonation of an α,β-unsaturated acylammonium intermediate. 30 We anticipated generation of the unsaturated acylammonium 3 through catalytic, asymmetric activation of acid chlorides by a chiral amine nucleophile (Fig.…”
mentioning
confidence: 99%
“…
Abstract: A straightforward synthesis of optically active trifluoromethyl dihydropyranones and spirocyclic oxindole-dihydropyranones has been realized by the chiral N-heterocyclic carbenes-catalyzed cy-A C H T U N G T R E N N U N G clization of a,b-unsaturated b-methylacyl chlorides with activated trifluoromethyl ketones or isatin derivatives.Keywords: asymmetric catalysis; cyclization; dihy-A C H T U N G T R E N N U N G dropyranones; N-heterocyclic carbenes; organocatalysis; vinylketenes Since Staudingers discovery of ketenes and the cycloaddition of ketene with imines to form b-lactams in early 1900s, [1] the cycloaddition reactions of ketene have become one of the powerful methodologies for construction of cyclic compounds.[2] In last decades, the catalytic enantioselective [2 + 2] or [2 + 4] cycloaddition of ketenes with aldehydes, [3] imines, [4] azo compounds, [5] nitro compounds, [6] oxadienes, [7] and azadienes [8] had been well established. In 2008 and later, we, [9] independently with Smith et al, [10] have demonstrated that N-heterocyclic carbenes (NHCs) [11] were efficient catalysts for the formal cycloaddition reactions of ketenes.
…”
mentioning
confidence: 99%